The role of cities in the foreign policy of emerging powers: the cases of Bogotá, Colombia and Johannesburg, South Africa - Delgado Caicedo, Jerónimo (Department of Environmental and Geographical Science, 2019)
Cities are increasingly important actors in the current International System. Cities fall under the jurisdiction of States where they play a fundamental role in the making and consolidation of emerging powers. In today’s State-centred International System, cities are underexamined in the field of foreign policy, a domain that is exclusively that of national governments. Using the cases of Colombia (Bogotá) and South Africa (Johannesburg), this thesis draws from multilingual sources to examine the role of cities in the foreign policy of emerging powers of the Global South. An interdisciplinary approach indicates that, by drawing together debates across International Relations and Urban Studies literature, there is little to no place for the conceptual and operational cross pollination necessary to engage the increasing importance of cities in the emerging powers of the Global South. The weak interface between cities and States in foreign policy is thus failing to inform local-national government interactions over global positioning and masks critical national actors in the evolution of cities. Through a geopolitical analysis, this thesis engages the conceptual and operational ambiguity around 'emerging powers’ by demonstrating how at both the national and city scale notions of 'power resources’, 'leadership’ and 'international recognition’ are actualised in the emerging powers of Colombia and South Africa. By tracking the ways that Bogotá and Johannesburg operate internationally, cities are, despite the lack of formal acknowledgement or endorsement of the nations’ foreign affairs machinery, shown to be crucial contributors to their countries’ emergence in the world. An analysis of primary sources in both Colombia and South Africa shows a mismatch between the city and the State in foreign policy caused by dynamics occurring both at national and local levels. The constitutional and legal ambiguities on decentralisation and foreign policy found in Colombia and South Africa make it extremely difficult to determine the how far sub-national entities can go in their burgeoning international engagements. The State-centred approach to foreign policy that is found in both countries contributes greatly to a general disregard for the city in international relations. Finally, the thesis reveals how the increased importance of cities in the global agenda and the proliferation of international associations of cities provides emerging cities such as Bogotá or Johannesburg with an alternative space in which to defend their own city interests without the help of the national governments. The thesis concludes by demonstrating that, while it is important that national governments make sure cities have a voice in the International System, changes also need to be made at the domestic level, both in national and local governments, in order to achieve functioning levels of understanding and co-operation between the city and the State in the making and implementation of the foreign policy of emerging powers.